The Design of Traceability Information System of Smart Packaging-Based Product Supply Chain to Improve A Competitiveness of Apple Processed Agro-Industry - Amalia, Faizatul; Kurniawan, Miftakhurrizal; Setiawan, Danang Triagus (Journal of Information Technology and Computer Science, 2020)
Agricultural food products are various. Apple is one of the agricultural product which is popular in Malang. There are many processed products from apple. However, there is a problem of food security concerning on the agricultural processed products. The food security consists of the information of nutrition contained in it, expired period, and the supply of healthy food. Therefore, it is required a traceability system that gives a guarantee about product authenticity and entrusted information about the food products. Lack of good information and infrastructure will hamper the formation of an effective traceability system that has not been considered even considered to require high costs, especially for some Small and Medium Enterprises (SME) producers. In general, producers and consumers need an information system that can provide food information effectively and efficiently. In general, producers and consumers need an information system that can provide food information effectively and efficiently. The design concept uses object oriented methods using United Modeling Language (UML), which consists of: Use Case Diagrams, Sequence diagrams and Class Diagrams. The design results were tested using Requirement Traceability Matrix (RTM) and the value of Response for a Class (RFC). Based on this test, it is produced that the RTM can be traced to all artifacts that have been made and the average RFC value is 5.17 meaning the RFC value is between 1 to 69, so that the RFC between 1 to 69 then the coupling is adaptable